2018
DOI: 10.1007/s00167-018-5327-2
|View full text |Cite
|
Sign up to set email alerts
|

Using chloroprocaine for spinal anaesthesia in outpatient knee-arthroscopy results in earlier discharge and improved operating room efficiency compared to mepivacaine and prilocaine

Abstract: Purpose Knee arthroscopies are regularly carried out in an outpatient setting. The purpose of this retrospective analysis was to investigate the impact of different local anaesthetics for spinal anaesthesia on operating room efficiency (perioperative process times) and postoperative recovery. This study aims to determine the optimal LA for SPA in patients undergoing knee arthroscopy at a day-surgery centre. Methods Anaesthesia records of all patients undergoing knee arthroscopy under spinal anaesthesia from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
(35 reference statements)
2
8
0
Order By: Relevance
“…In this cohort, chloroprocaine use was associated with increased OR efficiency, as seen by the shorter operative time for patients who received chloroprocaine. These findings mirror those found in knee arthroscopy studies where chloroprocaine was compared with other short-acting local anesthetics [15]. As discussed by Gebhardt et al [15], the shorter operative time in the chloroprocaine cohort may be a reflection of an improved interdisciplinary team effort and increased effort by surgeons to keep operative times as short as possible, as the shorter duration of action of the spinal may inspire surgeons to perform cases more efficiently, with less teaching.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…In this cohort, chloroprocaine use was associated with increased OR efficiency, as seen by the shorter operative time for patients who received chloroprocaine. These findings mirror those found in knee arthroscopy studies where chloroprocaine was compared with other short-acting local anesthetics [15]. As discussed by Gebhardt et al [15], the shorter operative time in the chloroprocaine cohort may be a reflection of an improved interdisciplinary team effort and increased effort by surgeons to keep operative times as short as possible, as the shorter duration of action of the spinal may inspire surgeons to perform cases more efficiently, with less teaching.…”
Section: Discussionsupporting
confidence: 65%
“…These findings mirror those found in knee arthroscopy studies where chloroprocaine was compared with other short-acting local anesthetics [15]. As discussed by Gebhardt et al [15], the shorter operative time in the chloroprocaine cohort may be a reflection of an improved interdisciplinary team effort and increased effort by surgeons to keep operative times as short as possible, as the shorter duration of action of the spinal may inspire surgeons to perform cases more efficiently, with less teaching. The shorter operative times may also reflect a lower case complexity in the group selected to receive chloroprocaine, which was not reflected in the comparison of baseline demographics of matched groups.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…These studies also reported the benefit of spinal chloroprocaine with a faster recovery of patients' autonomy. Data in ambulatory orthopedic surgery suggest that chloroprocaine is a reliable and sufficient anesthesia [11]. Camponovo and colleagues [12] showed that onsets of unassisted ambulation and hospital discharge were significantly faster in patients receiving chloroprocaine compared to patients receiving bupivacaine.…”
Section: Introductionmentioning
confidence: 99%